Práticas do dissenso: intervenções artísticas nos espaços públicos - Cruz, Pâmella Mochiute (2017)
The present research aims to reflect on the appropriation of public spaces through artistic interventions carried out by art collectives and artists from the city of São Paulo, with activities in the region of Centro and Barra Funda, from 1994. The Nelson Brissac’s Art/City project is adopted as period, as well as its resonances: the experience in Collective Pi, from 2009 to 2016, and participation in the research “Cultures and City: Theories and Project”, from 2015 onwards. For this purpose, we developed a mapping of works with urban wandering practices, using the conceptualization of Paola Berenstein Jacques (2014). Therefore, the study discusses the relevance of the relations between formal practices and informal occurrences in the understanding of territorial dynamics, contributing to an observation and a critical and sensitive action in the constructions and redefinitions of the public spaces of the city.